Back Cover: Ultra‐high performance separation of basic compounds on reversed‐phase columns packed with fully/superficially porous silica and hybrid particles by using ultraviolet transparent hydrophobic cationic additives. Issue 9 (25th May 2020) - Manetto, Simone; Mazzoccanti, Giulia; Ciogli, Alessia; Villani, Claudio; Gasparrini, Francesco
Abstract : DOI: 10.1002/jssc.201901333 The cover shows that, working at low pH elution conditions, the tetrabutylammonium additive produces a dynamic positive charged layer on stationary phase stabilized by hydrophobic and electrostatic interactions, and masks unfavourable interactions with silanols. In this way, the basic analyte amitriptyline, positively charged in the elution conditions, can elute faster, thanks to electrostatic repulsion, from chromatographic column providing very symmetrical peak. The approach has been specifically designed for basic analytes in RP‐UHPLC regime.